Migraine, tension-type headache, and attention-deficit/Hyperactivity disorder in childhood: A population-based study - Arruda, Marco Antônio; Arruda, Renato; Guidetti, Vincenzo; Bigal, Marcelo Eduardo (Headache Medicine, 2017)
Short Communication